Programme death ligand 1 expressions as a surrogate for determining immunotherapy in cervical carcinoma patients (2022)
Background The programme death ligand1 and its receptor (PD-1/PD-L1) interaction is a target for block age by immunotherapy that uses the body’s own immune system. Some studies show that PD-L1 expressing tumours are also more aggressive with poor prognosis. This study evalu ated the immunohistochemical expression of PD-L1 in uterine cervical carcinomas. Women with cervical cancer would benefit from its use as a marker in therapy and prognosis. Methods Hospital-based cross-sectional retrospective study was conducted. The study materials included 183 archived formalin fixed and paraffin embedded (FFPE) tissue blocks with histo logical diagnosis of cervical carcinoma diagnosed in our facility within a five-year period (January 2012 and December 2016) that met the study criteria. Data were extracted from records in the Department and immunohistochemistry was done using polyclonal antibodies to PD-L1 (GTX104763, Genetex). Obtained data were analysed using SPSS version 23. P < 0.05 was considered significant. Results A hundred and eighty-three cases of cervical cancer were studied. PD-L1 was positive in 57.4% of all cases. The diffuse pattern of staining was the major pattern accounting for 88.5% of positive cases. Poorly differentiated cervical carcinomas are less likely to express PD-L1. Within the histologic types, the squamous cell carcinomas expressed PD-L1 in 58.7%, and 50% of adenocarcinomas were positive. PD-L1 was not expressed in all cases of adenoid cystic carcinomas and basaloid squamous cell carcinomas. Conclusion A significant population of cervical carcinoma expresses PD-L1 by immunohistochemistry. PD L1 prevalence is lower amongst the poorly differentiated cancers compared to other grades.